Effect of sheep manure, vermicompost and biofertilizer on productivity of dill (Indian Journal of Arid Horticulture, 2025)
A field experiment was conducted to study the effect of sheep manure, vermicompost and biofertilizers on productivity of dill (Anethum graveolense L.) at NRC Seed Spices, Ajmer (Rajasthan) during rabi 2005-06 and 2006-07.The experiment consisted sixteen treatments comprising of control, three levels of sheep manure (5.0, 7.5, and 10.0t ha'), vermicompost (2.0, 3.0, and 4.0 t ha') and recommended fertilizer with and without biofertilizer. The results revealed that application of sheep manure, vermicompost and recommended fertilizer with and without bio-fertilizer proved superior over control. Moreover application of biofertilizer alone and with sheep manure, vermicompost and recommended fertilizer resulted in higher growth parameters, yield attributes and yield of dill over control. The increasing levels of sheep manure and vermi compost exhibited higher yield over their respective lower doses. The highest seed yield (15.25 q ha'), stover yield (32.12 q ha') and biological yield (47.37 q ha1) of dill was obtained with application of sheep manure @ 10 t ha-' with bio-fertilizer.
Keywords: Dill, bio-fertilizer; sheep manure; vermi-compost; fertilizer